Pengaruh Pemberian Jus Alpukat dengan Air Kelapa Muda pada Penderita Hipertensi Usia 60-74 tahun - Mika Rizki Diniaty; Septiani Septiani (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2022)
Hypertension is blood pressure above normal as indicated by systolic blood pressure > 140 mmHg and diastolic pressure > 90 mmHg. The risk factors for hypertension are age, gender and lack of potassium intake. Avocados and young coconut water are high sources of potassium. This study aimed to determine the effect of avocado juice with young coconut water on the blood pressure of elderly people with hypertension. The respondents of this study were 16 people based on the inclusion of the study, namely elderly people with hypertension who were willing to be research respondents aged 60 to 74 years and did not take antihypertensive drugs for the last one week. The intervention was given as much as 150 ml every morning with a potassium content of 1,500 mg. Analysis of the data used is the paired t-test. The results showed that the p-value of systolic and diastolic was 0.00 or < 0.05 so it could be concluded that there was a decrease in blood pressure in the elderly with hypertension and it was hoped that avocado juice with young coconut water would be an alternative non-pharmacological antihypertensive treatment.